2021
DOI: 10.1093/geront/gnab178
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Instruments Measuring Dyadic Communication and Environment in Dementia Care: A Systematic Review

Abstract: Background and Objectives A valid and reliable assessment of dementia dyadic communication and environment is essential to understand and facilitate social interaction and quality care. This review described the characteristics and evaluated psychometric properties of instruments that assess dyadic communication and environment between persons living with dementia and their caregivers. Research Design and Methods A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In this review, we used the PAT to evaluate the psychometric quality of the included instruments. The PAT was used in our prior systematic reviews of instruments and showed evidence of feasibility and ease of use ( Kim & Liu, 2021 ; Kim et al, 2022 ; Liu & Kim, 2021 ; Liu et al, 2021 ). Overall, included instruments were evaluated as having low psychometric quality except for RSST, SRS, and DSS, which assess swallowing ability and were scored as having moderate psychometric quality.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we used the PAT to evaluate the psychometric quality of the included instruments. The PAT was used in our prior systematic reviews of instruments and showed evidence of feasibility and ease of use ( Kim & Liu, 2021 ; Kim et al, 2022 ; Liu & Kim, 2021 ; Liu et al, 2021 ). Overall, included instruments were evaluated as having low psychometric quality except for RSST, SRS, and DSS, which assess swallowing ability and were scored as having moderate psychometric quality.…”
Section: Discussionmentioning
confidence: 99%
“…The item definitions and the coding rationale of the DCODE were developed from existing instruments and the literature describing communication behaviors in dementia populations. 8 , 9 The pool of items was initially developed through a comprehensive literature review. The items were reviewed by 6 experts specialized in nursing, communication, dementia, and family caregiving to evaluate item relevancy, clarity, specificity, and feasibility to establish face and content validity.…”
Section: Methodsmentioning
confidence: 99%
“…Other dyadic instruments found in the literature were developed without a conceptual framework and without consideration of type of communication. 9 Moreover, the DCODE assesses 3 categories of communication, including positive, negative, and neutral communication. Communication is a dynamic process with specific context-dependent behaviors (ie, neutral communication).…”
Section: Communication Patterns In Dementia Family Carementioning
confidence: 99%